Peningkatan Efektivitas Komunikasi Internal untuk Mendukung Operasional The Aula Coffee Club - Emmanuella Ivana Wibowo; Nur Hikmah Briliana Pradita Dewi; Salsabila Salsabila; Tika Widiyanti; Wulan Aribah (Sinergi Abdimas Jurnal Pengabdian Masyarakat, 2026)
Effective communication plays an important role in supporting operational activities and service quality in micro, small, and medium enterprises (MSMEs). This community service activity aimed to identify opportunities to improve internal communication at The Aula Coffee Club. The study employed a qualitative approach through interviews, observations, and documentation. The results indicated that internal communication had been carried out through regular briefings and operational communication groups. However, there were still opportunities to improve information delivery and coordination among staff. Therefore, several recommendations were proposed, including the development of internal communication standard operating procedures (SOPs), regular briefings, and an information confirmation system to minimize potential miscommunication. These efforts are expected to enhance communication effectiveness and support better service quality at The Aula Coffee Club.